Persönliche Erinnerungen an Hugo Rahner - Vorgrimler, Herbert (Zeitschrift für katholische Theologie, 2000)
The article records concrete impressions of the own studies and of personal encounters with H. R. So differences in teaching and thinking between the two Rahner brothers can be seen clearer, but also what links both together in life and academic work. The edition of the great volume in honour of H. R. procured by the author gives also much light about the high esteem of the church-historian in outstanding circles of the learned world of the time before II Vatican Council and also on an image of the church not yet renewed by "Lumen gentium".